2019
DOI: 10.1038/s41591-019-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of cancer patients enables personalized combination therapy: the I-PREDICT study

Abstract: Cancer treatments have evolved from indiscriminate cytotoxic agents to selective genome- and immune-targeted drugs that have transformed outcomes for some malignancies. 1 Tumor complexity and heterogeneity suggest that the “precision medicine” paradigm of cancer therapy requires treatment to be personalized to the individual patient. 2 – 6 To date, precision oncology trials have been based upon molecular matching with predetermine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
520
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 504 publications
(580 citation statements)
references
References 46 publications
15
520
2
9
Order By: Relevance
“…Of the 13 positive cases, 46% had PFS that was sufficiently long to meet the primary endpoint and 31% experienced objective treatment response (15% of the total study population). Other recent PCM studies in the refractory solid tumor setting have reported ORR of 0-11% for the total patient populations [4,[6][7][8][10][11][12][13], underpinning that the revised strategy of the MetAction study was advantageous. Overall survival was essentially similar for patients who did and did not receive study treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 positive cases, 46% had PFS that was sufficiently long to meet the primary endpoint and 31% experienced objective treatment response (15% of the total study population). Other recent PCM studies in the refractory solid tumor setting have reported ORR of 0-11% for the total patient populations [4,[6][7][8][10][11][12][13], underpinning that the revised strategy of the MetAction study was advantageous. Overall survival was essentially similar for patients who did and did not receive study treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The TARGET study in the United Kingdom analyzed patients' circulating tumor DNA as template for molecularly matched therapy and resulted in ORR of 36% for treated patients and 4% for the total cohort [11]. The I-PREDICT study in the United States exploited several genetic alterations in the tumor and circulation to propose combinations of therapies, resulting in ORR of 20% for treated and 11% for all tested patients, and improved PFS when the theoretical concordance between actionable mutations and the chosen therapies (the matching score) was high [12]. The multinational WINTHER trial applied either large-scale DNA sequencing or RNA expression analysis of fresh metastasis specimens, resulting in ORR of 11% for treated patients and 4% for the total cohort, with median PFS of 2 months but again significantly longer for patients with high matching score [13].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of the use of NGS in cancer clinical care and research has resulted in significant improvement in outlook for a subset of malignancies [216][217][218]. Indeed, genomic markers can drive new clinical trials of both gene-and immune-targeted agents [219][220][221][222][223][224][225]. Relatively new, however, is the emergence of data showing that non-cancerous illnesses also have genomic markers, and intriguingly, that some of these molecular alterations are indistinguishable from those considered oncogenic drivers for certain malignancies.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…The use of open-label basket clinical trials, in which patients are matched with drugs on the basis of a genomic aberration (regardless of histology), has been effective in a variety of cancer settings [16,[226][227][228][229]; similar approaches could conceivably be taken in benign conditions, for which trials that are disease agnostic could be developed and drug choice would be dictated by the genomic aberration. Alternatively, individual sequencing studies of somatic or germline tissue may define the treatment prosecution strategy on an N-ofone basis in selected non-malignant diseases, as it is beginning to do in malignancy [223]. Regardless, patients would require close follow-up to determine whether their cancer risk was modified by the use of matched targeted agents, and functional studies on tissues might help to identify those conditions that are most likely to respond to cognate compounds.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…Meta-analysis of Phase I clinical trials completed during 2011-2013 showed that on the whole, trials that used molecular biomarker information to influence treatments gave better results than trials that did not (Schwaederle et al 2016). However, most precision oncology treatments utilize only one or two treatments, and resistant clones frequently emerge, emphasizing the need to deliver personalized medicine as multiple treatments combined together (Arnedos et al 2014;Schwaederle et al 2016;Nikanjam et al, 2017;Rebollo et al 2017;Sureda et al 2018;Sicklick et al 2019).…”
Section: Introductionmentioning
confidence: 99%